INSIGHT OF YOUNG INDIAN CUSTOMERS ON “GREEN LABELING” STRATEGY – AN EMPRICAL ANALYSIS - Kumar, B. Dinesh; Kajapriya, R. (International Journal of Psychosocial Rehabilitation, 2020)
A young customer insight on any business product is depends on several factors and that may change over the time, since the technological advancement in India leads the young generation to update themselves on all forms of businesses and its strategies. In recent days, customers being to concern about global environment and that made a change in their purchase decisions. This change lead many businesses to concentrate on the ecological customers buying behaviour and are emerging with green labels or eco labels which become an influencing factor in customers purchase decision. This study is to understand the theoretical framework of young customer’s insight on green labeling, to analyse the types of green labeling available throughout the world, to examine the familiarity of the customers on green labeling and the reason for purchasing green labelled products and perception of customers towards the eco labelled businesses.